Long non‐coding RNAs expression profiles in hepatocytes of mice after hematopoietic stem cell transplantation. Issue 3 (24th January 2016) - Qiao, Jianlin; Yao, Haina; Xia, Yuan; Chu, Peipei; Li, Mingfeng; Wu, Yulu; Li, Wen; Ding, Lan; Qi, Kunming; Li, Depeng; Xu, Kailin; Zeng, Lingyu
Abstract: Hepatic veno‐occlusive disease (HVOD), one serious complication following hematopoietic stem cell transplantation (HSCT), is mainly initiated by the damage to sinusoidal endothelial cells and hepatocytes. Long non‐coding RNAs (lncRNAs) play an important role in the proliferation of hepatocytes and liver regeneration. lncRNAs profile in hepatocytes post‐HSCT remains unclear. The aim of this study is to evaluate the profile of lncRNAs in hepatocytes of mice after HSCT. Mice HSCT model was established through infusion of 5 × 10 6 bone marrow mononuclear cells. On day 7, 14 and 33 after HSCT, mice were sacrificed for analysis of liver pathology, function and index. Total RNA was extracted from hepatocytes of mice on day 14 for microarray analysis of the expression profiles of lncRNAs by Arraystar Mouse lncRNA Microarray v2.0. Obvious edema and spotty necrosis of hepatocytes with inflammatory cells infiltration were observed post‐HSCT. Meanwhile, increased levels of alkaline phosphatase, aspartate transaminase, and total bilirubin, as well as elevated liver index were also found. 2, 918 up‐regulated and 1, 911 down‐regulated lncRNAs in hepatocytes were identified. Some of differentially expressed mRNAs had adjacent lncRNAs that were also significantly dysregulated, with the same dysregulation direction. T‐cell receptor (up‐regulation) and VEGF signaling pathway (down‐regulation) were identified as one of the most enriched pathways. Dysregulated lncRNAs might be involved in hepatocytes damage after HSCT, suggesting targeting them might be a novel approach in amelioration of hepatocytes damage. © 2016 IUBMB Life, 68(3):232–241, 2016